2020
DOI: 10.1038/s41598-020-60267-0
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study: The Association Between Autoimmune Disorders and Leptospirosis

Abstract: & cheng-Yoong pang 6,7,8* there are limited studies on the association between systemic autoimmune rheumatic diseases (SARDs) and leptospirosis. Therefore, this study aims to identify the effects of leptospirosis on the risks of developing SARDs with a nationwide retrospective cohort study. Patients with leptospirosis who did not have a diagnosis of SARDs before the index date were enrolled from the Taiwan National Health Insurance Research Database between 2000 and 2010, as the leptospirosis cohort. For each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Given that ATP-binding proteins are essential for Leptospira and H. hepaticus, the identification of such protein from these species indicates the potential significant role of such species for T2D pathogenesis. In 2020, a systematic analysis confirmed the potential association between autoimmune disorders (including T2D) and Leptospira infection (Teh et al, 2020). Another independent research also validated that the infection of Leptospira is associated with diabetic chronic kidney disease (Carrillo-Larco et al, 2019).…”
Section: Optimal Orthologous Gene/protein Features Annotated By Eggnog Databasementioning
confidence: 88%
“…Given that ATP-binding proteins are essential for Leptospira and H. hepaticus, the identification of such protein from these species indicates the potential significant role of such species for T2D pathogenesis. In 2020, a systematic analysis confirmed the potential association between autoimmune disorders (including T2D) and Leptospira infection (Teh et al, 2020). Another independent research also validated that the infection of Leptospira is associated with diabetic chronic kidney disease (Carrillo-Larco et al, 2019).…”
Section: Optimal Orthologous Gene/protein Features Annotated By Eggnog Databasementioning
confidence: 88%
“…However, these reports were either of small case numbers or outbreak series. An earlier study argued that onset of many autoimmune diseases would develop after Leptospira infection (23). They found that patients with prior leptospirosis were at increased risk of subsequently developing many autoimmune diseases (up to 18 autoimmune diseases).…”
Section: Introductionmentioning
confidence: 99%